Milk and marketing of dairy productions in Samangan province: A case study in districts of Khuram-Sarbagh, Feroz-Nakhchir, and center of Samangan (Aybak), Afghanistan - Mukhtar, Abdul Hadi; Ashkar, Sayed Batin; Azizi, Benazir (International Journal of Innovative Research and Scientific Studies, 2021)
In this study the status of milk and dairy production marketing in Samangan province is explained. Locking of ranchers accessing to a respondent dairy production market is the main problem focused herein. In Afghanistan illiteracy, traditional customs dominance and low economy level are the major gaps somewhat nationally remained unresolved among most of ranchers. The main objective of this study is assessing the dairy productions market situation to empower the economy level of farmers. A complex method was applied in this study including observation, interview, and questionnaire. Totally 117 questionnaires were handled. Results of analyzed collected data clarify that 90% of ranchers were illiterate, dairy cattle keeping is more than other milky animals because of its lower needs to silage and land. It has been concluded that farmers of Samangan province have adequate experience of keeping and nourishing the domestic animals in order to get a noticeable income. For getting the highest income and having modernized dairy production activities, from the viewpoint of authors, gradually researches accommodating are recommended and this research findings and conclusions will contribute better designing of the future research.